PENGARUH SUBSTITUSI KEDELAI DENGAN BIJI LAMTORO (Leucaena leucocephala) PADA TEMPE TERHADAP KANDUNGAN SERAT, GLUKOMANAN DAN FLAVONOID UNTUK PENDERITA DIABETES MELITUS TIPE 2 - Milda Rosita Mala (2023)
Lamtoro seeds contain high crude fiber, glucomannan, and flavonoids. In terms of reducing blood sugar levels Type 2 Diabetes Mellitus, these three nutrients play an important role. This research aimed to analyze the effect of substituting soybeans with lamtoro seeds in tempeh on proximate content, crude fiber content, glucomannan, and flavonoids and to determine the selected formula. This study used an experimental study with a one-factor Completely Randomized Design (RAL) method with two repetitions consisting of four treatment levels, namely F0 (0:100), F1 (40:60), F2 (50: 50), and F3 (60:40 ). Test the nutritional content using the ANOVA test. The results of the analysis showed that the substitution of soybeans with lamtoro seeds in tempeh had a significant effect (p = 0.039), on crude fiber content, had a significant effect (p = 0.000) on glucomannan levels, and had no significant effect (p = 0.236) on flavonoid levels. The best formula was F3 (60:40) as the selected formula. The serving size for the selected formula is 50 g, equivalent to 2 medium-sized pieces of tempeh, with a nutritional content of 72.47 kcal energy, 8.42 g protein, 2.63 g fat, 3.6 g carbohydrates, 2.3% crude fiber, 8.035% glucomannan, and 0.07% total flavonoids.